A Comparison of Urine Dipstick Test with Spot Urine Protein–Creatinine Ratio and 24-Hour Protein Excretion in Women with Pre-Eclampsia: Urine Dipstick Test with Spot Urine Protein–Creatinine Ratio in Women with Pre-Eclampsia - Shaheen, Nabila; Uzma, Syeda; Zainab, Sadia; Hayat, Naheed; Saleem, Asifa (Pakistan Journal of Health Sciences, 2025)
Pre-eclampsia is a major obstetric complication marked by hypertension and significant proteinuria after 20 weeks of gestation, posing serious maternal and fetal risks. Early and accurate detection is critical for effective management. Objectives: To assess the diagnostic accuracy, sensitivity, and specificity of the spot urine protein–creatinine ratio (UPCR) in detecting significant proteinuria in pre-eclamptic women, compared to 24-hour urine protein excretion. Methods: A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Tertiary Care Hospital, Bahawalpur, from November 24, 2022, to May 23, 2023 (Approval No. 1516/Trg/2022). The study included 202 pregnant women diagnosed with pre-eclampsia. Spot UPCR and 24-hour urine protein were measured, and dipstick testing was performed. A UPCR cutoff of 0.3 was used to evaluate diagnostic accuracy. Results: The mean UPCR was 1.47 ± 1.05 mg/g, and the mean 24-hour urine protein excretion was 1475.35 ± 1099.87. mg. Spot UPCR showed a strong correlation with 24-hour urine protein (r = 0.974, p<0.001). ROC analysis revealed an AUC of 0.971. At the 0.3 cutoff, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 84.2%, 83.3%, 98.8%, and 25.0%, respectively. Conclusions: It was concluded that spot UPCR is a reliable and efficient alternative to 24-hour urine collection for detecting significant proteinuria in pre-eclampsia. Its integration into routine antenatal care may enhance early diagnosis and improve maternal and fetal outcomes.